2022
DOI: 10.3390/diagnostics12112693
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Challenge: Detection of Cardiac Amyloidosis Based on Bi-Atrial and Right Ventricular Strain and Cardiac Function

Abstract: Background: This study challenges state-of-the-art cardiac amyloidosis (CA) diagnostics by feeding multi-chamber strain and cardiac function into supervised machine (SVM) learning algorithms. Methods: Forty-three CA (32 males; 79 years (IQR 71; 85)), 20 patients with hypertrophic cardiomyopathy (HCM, 10 males; 63.9 years (±7.4)) and 44 healthy controls (CTRL, 23 males; 56.3 years (IQR 52.5; 62.9)) received cardiovascular magnetic resonance imaging. Left atrial, right atrial and right ventricular strain paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…By putting cardiac function and multi-chamber strain into supervised ML algorithms, the work challenges CA diagnoses [ 85 ]. CMR imaging was performed on CA patients, HCM participants, and healthy volunteers.…”
Section: Diagnosis Of Amyloidosismentioning
confidence: 99%
See 1 more Smart Citation
“…By putting cardiac function and multi-chamber strain into supervised ML algorithms, the work challenges CA diagnoses [ 85 ]. CMR imaging was performed on CA patients, HCM participants, and healthy volunteers.…”
Section: Diagnosis Of Amyloidosismentioning
confidence: 99%
“…Using the strain values for the left, right, and right ventricular atriums as well as heart function, the decision trees (DT), k-nearest neighbor (KNN), SVM linear, and SVM radial basis function (RBF) kernel algorithms developed a 41-feature matrix. Using linear SVM and RBF, a 10-feature principal component analysis (PCA) was carried out [ 85 ]. As a result, under supervised conditions, the SVM RBF kernel obtained competitive diagnostic accuracies.…”
Section: Diagnosis Of Amyloidosismentioning
confidence: 99%
“…Another retrospective single-center study by Eckstein et al investigated the diagnostic performance of CMR imaging in detecting CA using ML algorithms [59]. The study used multi-chamber strain and cardiac function as input parameters for a 41-feature matrix decision tree and supervised ML algorithms.…”
Section: Ai Applications To Cardiac Magnetic Resonance In Cardiac Amy...mentioning
confidence: 99%
“…The study used multi-chamber strain and cardiac function as input parameters for a 41-feature matrix decision tree and supervised ML algorithms. Under supervised conditions, the support vector machine (SVM) algorithm demonstrated competitive diagnostic accuracies of 87.9% (AUC = 0.960) [59]. This suggests that ML of multi-chamber cardiac strain and function could provide innovative insights for non-contrast clinical decision-support systems in the diagnosis of CA.…”
Section: Ai Applications To Cardiac Magnetic Resonance In Cardiac Amy...mentioning
confidence: 99%
“…The study of the right atrial strain and strain rate performed by CMR also proved to be useful in distinguishing amyloid from hypertrophic cardiomyopathy [ 57 ]. Similary, the strain evaluation of biatrial chambers and right ventricle confirmed to be promising in early CA detection [ 58 ].…”
Section: Other Imaging Modalitiesmentioning
confidence: 99%